Anticonvulsant activity of ringed enaminones: a QSAR study - Garro Martinez, Juan Ceferino (2009)
The formalism of the QSAR Theory is employed to establish mathematical relationships that link the molecular structure of ringed enaminones to their observed antiepileptic activity. The design of predictive linear regression models, solely based on the available experimental information, involved the simultaneous analysis of 1312 theoretical descriptors calculated with Dragon software. This QSAR study that is based both on classic antiepileptics and second-generation anticonvulsant drugs, including compounds of the enaminone type, allowed the proposal of novel ringed enaminone derivatives as possible antiepileptic agents, posing a similar or even better predicted biological activity when compared to other commonly used drugs.